Effects of nature exposure intervention on self-regulation and decision-making in mentally-fatigued university soccer players - He, Sun (2021)
Mental fatigue is a psychobiological state induced by a prolonged duration of demanding cognitive tasks. The effects of mental fatigue on soccer performance have been well investigated in the literature. However, the intervention that can counteract mental fatigue and improve subsequent performance remains unclear, particularly when it comes to decision-making, which is most important skill in soccer. The objective of this study was to examine the impact of nature exposure on self-regulation, and decision-making among mentally fatigue university players. A true experimental design. was utilized in the study. Ninety male university soccer players aged 18-24 years were selected with a simple random sampling technique. And all of them were randomly assigned into six groups (n=15 each group) with comparisons of three different durations of nature exposure intervention (4.170 min, 8.330 min and 12.500 min) in experimental groups and corresponding control groups. All subjects viewed virtual pictures on a computer. Prior to the intervention, a 45 min computer-version Stroop task was used to induce mental fatigue condition. Results from two-way repeated ANOVA and ANCOVA procedures suggested that nature exposure had significantly improved the players’ heart rate variability (F = 6.284, P = 0.014, 2 = 0.070); cognitive and physical anxiety (F = 4.567, P = 0.001, 2 = 0.216) and state confidence (F = 5.077, P<0.001, 2 = 0.232) of competitive state anxiety; as well as reaction time of decision-making (F = 4.755, P = 0.001, 2 = 0.221). Specifically, Exp 3 not only showed the improvement from pre-test to post-test, but improved significantly in heart rate variability (1.521±0.805 vs. 2.640±0.858), cognitive and physical anxiety (30.267±7.411 vs. 41.200±9.306), state confidence (30.267±3.575 vs. 25.267±4.935), and reaction time of decision-making (5.011±1.457 vs. 7.213±1.652) compared with control group at post-test. Moreover, Exp 2 only showed the significant improvement from pre-test to post-test. To contrast, there was no significant improvement in Exp 1 (p>0.050) in three dependent variables. Inline, the mental fatigue condition decreased to the lowest level among six groups in Exp 3, followed by Exp 2. The mental fatigue condition only had a slight decrease in Exp 1. Overall, nature exposure significantly improved self-regulation and decision-making in mentally fatigue university soccer players. However, depending on the duration of the intervention when nature scenes are fixed. The best duration to improve self-regulation and decision-making in this study was 12.50 min. Additionally, the attention can be the third option in the psychobiological model of exercise performance to apply in the sport skilled performance (e.g., decision-making).